Influence of laboratory-related and endoscopy-related factors on the assessment of serum pepsinogens and gastrin-17. Issue 12 (December 2017) - Goni, Elisabetta; Venerito, Marino; Schulz, Christian; Weigt, Jochen; Langner, Cosima; Link, Alexander; Malfertheiner, Peter
Abstract : Background and aim: Serum pepsinogen I (PGI) and pepsinogen II (PGII) are noninvasive parameters in the detection of atrophic gastritis. The diagnostic add-on value of serum gastrin-17 (G-17) remains uncertain. The aim of this study was to assess the stability of these serum parameters over time and to evaluate the influence of clinical factors, such as upper gastrointestinal (GI) endoscopy and bowel cleansing, on serum PGI, PGII, and G-17 assessment. Patients and methods: A prospective study was carried out in healthy individuals and patients. For the stability analyses, the plasma and serum samples from 23 individuals were processed at different time points with and without the addition of a stabilizer. Ten patients were included to evaluate the influence of upper GI endoscopy and 18 patients to evaluate the effect of bowel cleansing before colonoscopy. Results: PGI, PGII, and G-17 levels were not statistically different in the serum and plasma. PGI and PGII serum levels were stable over time. G-17 is associated with time-dependent degradation ( P =0.0001). The addition of the G-17 stabilizer showed no improvement in stability. Upper GI endoscopy and bowel preparation before colonoscopy were associated with minimal variations in PGI and PGII, whereas G-17 showed patient-specific alterations. Conclusion: PGI and PGII serum levels are stable over time. However, G-17 stability is strongly dependent on the time of processing and storage; therefore, samples for G-17 analysis need to be processed no later than 6 h after blood collection. Upper GI endoscopy and colonoscopy preparation lead to minimal nonsignificant changes in basal PGI, PGII, and G-17 levels.